Soil incorporation of trash and foliar application of plant growth regulators boosted sugarcane ratoon yield - Rai, Rama Kant; Singh, Pushpa; Suman, Archna; Shukla, L. (Indian Farming, 2018)
Ratooning practice saves cost on preparatory tillage and planting material and benefits from the residual manure and moisture. However, yields are generally found to be lower than plant crop in the successive years under normal conditions. Usage of trash generated from the plant crop of sugarcane reduced soil compaction and improved the availability of nutrients and moisture. Application of PGRs at various growth stages further mitigates the adverse effects of tiller mortality and poor assimilate accumulation and partitioning towards stalk. In situ decomposition of sugarcane trash (dispersed @ 12 tonne/ha) generated form the plant crop with Pusa compost inoculant (@ 300 g/ tonne of trash) and foliar applications of Ethrel and GA3 at 60, 90, 120 and 150 diammonium phosphate increases tiller numbers during grand growth stage, reduces tiller mortality, increases NMC and ratoon crop yield by about 16.9 tonne/ha.